The Influence of Religious Activities on Solidarity and Social Care of Muslim Teenagers - Alya Rahmania; Nabila Nabila (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2026)
Religious activities play an important role in shaping the social and moral character of Muslim adolescents. Amid the rapid development of digital technology and the growing tendency toward individualism, religious activities serve as an effective medium for fostering social solidarity and social awareness. This study aims to analyze the influence of religious activities on the development of social solidarity and social concern among Muslim adolescents and to examine their relevance in contemporary social life. This research employs a qualitative descriptive approach using a library research method. Data were collected from books, scholarly journals, and previous studies relevant to the topic. The findings indicate that active participation in religious activities, such as congregational prayers, Islamic study circles, mosque youth organizations, and community-based religious programs, contributes significantly to strengthening ukhuwah Islamiyah (Islamic brotherhood), enhancing empathy, and fostering social responsibility among adolescents. Furthermore, religious activities help reduce individualistic behavior and promote social cohesion in the face of challenges posed by the digital era. Therefore, religious activities function not only as a means of spiritual development but also as an effective instrument for cultivating social solidarity and social awareness among Muslim adolescents.